Information acquisition during a Dutch auction - Paavo Miettinen (Bank of Finland, 2010)
In this paper we consider equilibrium behavior in a Dutch (descending price) auction where the bidders are uninformed of their valuations with probability 1-q and can acquire information about their valuation at a positive cost during the auction. We assume that the information acquisition activity is covert. We characterize the equilibrium behavior in a setting where bidders are ex ante symmetric and have independent private values. We show that, if the number of bidders is large, the Dutch auction produces more revenue than would a first price auction.
URN:NBN:fi:bof-20140807382; More recent version: http://hdl.handle.net/10419/212211
Keywords: 330